Penerapan Sistem Reward dan Punishment dalam Perspektif Konsep Mashlahah - Parman Parman; Ismail Ismail; Adi Maulana Rachman (Glossary : Jurnal Ekonomi Syariah, 2023)
In essence, in the world of work, of course, it is very necessary for human resources who have a work ethic with high motivation to increase work productivity and as a form of real example of a commitment in order to achieve the goals that have been set. To improve and make morale (work ethic) always present and tend to grow, one of the things that is very important to pay attention to is implementing a reward and punishment system. The policy of implementing rewards and punishments is expected to be a stimulus to improve the culture of maximum performance because performance is a real behavior displayed by each employee as an achievement in accordance with his role (rights and obligations) in an agency. The concept of mashlahah is the path taken by Islamic law to implement His rules and commandments against new events that are not accommodated in the nash, as an effort to create goodness that is long-term (hereafter dimension) and short-term (worldly dimension), material and spiritual and includes collective and individual aspects. In addition, three main elements must be fulfilled, namely sharia compliance (halal causa), having benefits and bringing goodness (thayyib) in various aspects universally that do not cause harm.